Evaluation of Optimization of Drug Therapy in Heart Failure Patients with reduced ejection Fraction in the Outpatient Department and Emergency Department of a Central Hospital - Poudel, Samir Kumar; Gautam, Binayak; Sherpa, Kunjang; Chapagain Koirala, Prabha; Mishra, Deepak Kumar; Subedi, Manoj; Ghimire, Saroj; Gautam Poudel, Lata (Nepalese Heart Journal, 2025)
Background: Heart failure with reduced ejection fraction (HFrEF) is a significant global healthcare burden. However, limited data exists on management patterns and outcomes in heart failure in the Nepalese healthcare context. This study aimed to evaluate the baseline characteristics, guideline-directed medical therapy (GDMT) utilization, shortcomings and treatment outcomes in HFrEF patients at a tertiary care center in Nepal. Methods: This was a prospective observational study conducted on 96 consecutive patients diagnosed with HFrEF. Demographic characteristics, clinical presentation, drug prescriptions, dosing patterns and treatment outcomes were systematically analyzed. Optimal dosing was defined according to current international guidelines. Results: The study population had a mean age of 61.6 ± 12.9 years (range 20-90 years) with male predominance (64.6%). Most patients were middle-aged (41.7%) or elderly (41.7%), with 69.8% residing outside Kathmandu metropolitan area. Atrial fibrillation was present in 13.5% of patients. Two-thirds had been receiving treatment for heart failure for more than three months. The majority of patients presented in NYHA functional class II and III. GDMT prescription rates were high: beta-blockers 97.9% (metoprolol succinate 80.2%), RAAS inhibitors 81.25% (ARBs preferred over ACEi, 38.5% vs 24%), mineralocorticoid receptor antagonists 79.2% (spironolactone exclusively), and SGLT- 2 inhibitors 73.9% (dapagliflozin 51%, empagliflozin 22.9%). Loop diuretics were prescribed in 77% of patients (furosemide 64.6%). Anticoagulation with NOACs was used in 9.3% of patients, with no warfarin prescriptions. Despite high prescription rates, optimal dosing was achieved in a minority of patients. No patient received optimal doses of all GDMT components. Only 51% of patients achieved optimal dosing of two medications, while 30.2% achieved optimal dosing of one medication. Spironolactone demonstrated the highest optimal dosing rate (75%) followed by SGLT-2 inhibitors. Beta- blockers showed universal suboptimal dosing. Primary barriers to optimization included ongoing uptitration process (45.8%), hemodynamic unsuitability (16.6%), and physician inertia (10.4%). Clinical improvement was observed in 72.9% of patients, while 19.7% experienced clinical deterioration. The remaining patients maintained stable clinical status throughout the treatment period. Conclusions: This study unveils a paradox in HFrEF management in Nepal: excellent GDMT prescription rates coupled with universal suboptimal dosing. High utilization of evidence-based therapies, including rapid adoption of SGLT-2 inhibitors, is commendable. The systematic underdosing represents a critical quality gap prompting the healthcare system for its rectification. The favorable clinical outcomes in nearly three-quarters of patients suggest substantial potential for further improvement through systematic medication optimization strategies. These findings indicate the gravity of need for structured heart failure management programs that includes physician education initiatives and systematic uptitration protocols to bridge the gap between guideline recommendations and clinical practice in the Nepalese healthcare setting.